Positive electrode active material and preparation method thereof, positive electrode plate, all-solid-state lithium secondary battery and electric device
By covering the surface of the lithium transition metal oxide with rare earth bromide solid electrolyte to form an ion conductive layer, the problems of Coulomb efficiency and cyclic stability of lithium-ion all-solid battery are solved, and stability and efficient charge conduction are achieved at high voltages.
Patent Information
- Application Number
- CN202410217490.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2025-08-29
AI Technical Summary
The Coulomb efficiency and cycle stability of lithium-ion all-solid state batteries are poor, especially at high voltages, which can affect battery performance.
The surface of lithium transition metal oxide is coated with rare earth bromide solid electrolyte to form an ion conductive layer. The positive electrode active material is prepared under vacuum heat treatment by ammonium-assisted synthesis method to improve ion conductivity and enhance high voltage stability.
It improves the Coulomb efficiency and cycling stability of the positive electrode active material, reduces the risk of high voltage decomposition, broadens the charge and discharge voltage range, and improves the overall performance of the battery.
Smart Images

Figure CN120565672A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, an all-solid-state lithium secondary battery, and an electrical device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] In recent years, the application of lithium-ion batteries has become increasingly widespread. They are widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the rapid development of lithium-ion batteries, higher requirements have been placed on their energy density, cycle performance, and safety performance. Currently, the coulombic efficiency and cycle stability of lithium-ion all-solid-state batteries are poor. Summary of the Invention
[0004] The present application provides a positive electrode active material and a preparation method thereof, a positive electrode plate, an all-solid-state lithium secondary battery and an electrical device, which can improve the coulombic efficiency and cycle stability of the all-solid-state lithium secondary battery.
[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, comprising:
[0006] lithium transition metal oxides; and
[0007] An ion-conducting layer is coated on at least a portion of the surface of the lithium transition metal oxide, and the ion-conducting layer comprises a rare earth bromide solid electrolyte.
[0008] In some embodiments of the present application, the rare earth bromide solid electrolyte satisfies the chemical formula Li 6-3x R x Br6, 0.5≤x≤1.5, R includes at least one of Sc, Y, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu;
[0009] Optionally, 0.8≤x≤1.3;
[0010] Optionally, R includes at least one of Tb, Dy, Ho, Er, Tm, Yb and Lu.
[0011] In some embodiments of the present application, the mass proportion of the rare earth bromide solid electrolyte in the positive electrode active material is 5% to 30%, and can be optionally 8% to 20%.
[0012] In some embodiments of the present application, the thickness of the ion-conducting layer is 5 nm to 50 μm, and can be optionally 8 nm to 10 μm.
[0013] In some embodiments of the present application, the lithium transition metal oxide includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium cobalt oxide, lithium manganese oxide, and lithium-rich manganese-based positive electrode materials;
[0014] Optionally, the lithium transition metal oxide is lithium nickel cobalt manganese oxide.
[0015] In some embodiments of the present application, the ionic conductivity of the lithium transition metal oxide is 10 -7 S / cm~10 -4 S / cm.
[0016] In some embodiments of the present application, the ionic conductivity of the positive electrode active material is 10 -6 S / cm~10 -3 S / cm.
[0017] In some embodiments of the present application, the volume average particle size of the positive electrode active material is 1 μm to 30 μm.
[0018] The second aspect of the present application further provides a method for preparing the positive electrode active material described in the first aspect of the present application, comprising:
[0019] The rare earth bromide solid electrolyte is coated on at least a portion of the surface of the lithium transition metal oxide to form the ion-conducting layer to prepare the positive electrode active material.
[0020] In some embodiments of the present application, coating at least a portion of the surface of the lithium transition metal oxide with the rare earth bromide solid electrolyte comprises:
[0021] performing vacuum heat treatment on a mixture powder comprising the lithium transition metal oxide, ammonium bromide, lithium bromide, and rare earth bromide to form the rare earth bromide solid electrolyte on at least a portion of the surface of the lithium transition metal oxide, and to form the ion-conducting layer covering at least a portion of the surface of the lithium transition metal oxide;
[0022] Wherein, in the mixed powder, at least a portion of the surface of the lithium transition metal oxide is coated with the ammonium bromide, the lithium bromide and the rare earth bromide.
[0023] In some embodiments of the present application, the method for preparing the mixture powder includes:
[0024] Dissolving a rare earth compound and a lithium source in a hydrobromic acid solution to react and prepare a mixed solution containing the rare earth bromide and the lithium bromide;
[0025] The ammonium bromide and the lithium transition metal oxide are added to the mixed solution, followed by drying and pulverization to prepare the mixed powder.
[0026] In some embodiments of the present application, the molar ratio of the ammonium bromide to the rare earth element in the rare earth compound is (3-8):1.
[0027] In some embodiments of the present application, the method satisfies at least one of the following conditions:
[0028] (1) The pH value of the hydrobromic acid solution is 2-4;
[0029] (2) The molar ratio of the ammonium bromide to the rare earth element in the rare earth compound is (3-5):1.
[0030] (3) The temperature of the vacuum heat treatment is below 500°C, and can be selected from 430°C to 480°C.
[0031] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect of the present application.
[0032] The fourth aspect of the present application provides an all-solid-state lithium secondary battery, comprising the positive electrode sheet of the third aspect of the present application.
[0033] The fifth aspect of the present application provides an electrical device comprising the all-solid-state lithium secondary battery of the fourth aspect of the present application.
[0034] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery.
[0035] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims.
[0036] The positive electrode active material provided by the present application includes a lithium transition metal oxide and an ion-conducting layer, wherein the rare earth bromide solid electrolyte contained in the ion-conducting layer can not only improve the ionic conductivity of the lithium transition metal oxide, thereby improving its conductivity to active ions, thereby improving the coulombic efficiency of the positive electrode active material and the battery using the positive electrode active material. Moreover, since the rare earth bromide solid electrolyte has a relatively wider electrochemical window (wider than the sulfide solid electrolyte), it is more stable at high voltage, thereby effectively reducing the risk of high-voltage decomposition and improving the high-voltage resistance and cycle stability of the positive electrode active material and the battery using the positive electrode active material. Therefore, the positive electrode active material provided by the present application can take into account both ionic conductivity and high-voltage stability, which is conducive to achieving a simultaneous improvement in the coulombic efficiency and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to better describe and illustrate the embodiments or examples provided in this application, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes currently understood for these applications. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the accompanying drawings:
[0038] Figure 1 Schematic diagram of the preparation process of the positive electrode active material according to one embodiment of the present application.
[0039] Figure 2 Schematic diagram of an electrical device using an all-solid-state lithium secondary battery as a power source according to one embodiment of the present application. DETAILED DESCRIPTION
[0040] Below, some embodiments of the positive electrode active material and its preparation method, positive electrode sheet, all-solid-state lithium secondary battery and power device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0041] " scope " disclosed in the present application can be limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 listed, and if the maximum range value 3,4 and 5 are also listed, then the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is merely an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to listing the parameter as, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and so on. For example, when a parameter is expressed as an integer selected from "2-10", this is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0042] In this application, "a plurality of" or "a plurality of" refers to a number greater than or equal to 2 unless otherwise specified. For example, "one or more" means one or more than or equal to two.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0044] References to "embodiments" herein mean that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of such phrases in various locations in the specification does not necessarily refer to the same embodiment, nor does it necessarily refer to independent or alternative embodiments that are mutually exclusive with other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments. References to "implementations" herein have a similar understanding.
[0045] It will be appreciated by those skilled in the art that, in the methods of various embodiments or examples, the order in which the steps are written does not imply a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible inherent logic. Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0046] In this application, open technical features or technical solutions described with words such as "contain," "include," and "include" do not exclude additional members beyond the listed members, unless otherwise specified. This can be considered as providing both closed features or solutions consisting of the listed members and open features or solutions that include additional members beyond the listed members. For example, if A includes a1, a2, and a3, it may or may not include other members unless otherwise specified. This can be considered as providing both the feature or solution that "A consists of a1, a2, and a3," and the feature or solution that "A includes not only a1, a2, and a3, but also other members." In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0047] In this application, the terms "optionally," "optional," and "optional" are optional and refer to either option being present or absent. If a technical solution contains multiple "options," each option is considered independent unless otherwise specified and there are no conflicts or constraints.
[0048] In all-solid-state batteries, the interface contact problem is a pain point that limits their performance. Poor interface contact (between the positive electrode material and the electrolyte, between the negative electrode material and the electrolyte, between electrolyte particles, etc.) often leads to problems such as large interface impedance, more side reactions, and abnormal lithium precipitation. The positive electrode side of the all-solid-state battery often adopts a composite positive electrode model, which is uniformly composed of positive electrode active materials, solid electrolytes, and conductive agents in a certain ratio. Among them, the addition of solid electrolytes and conductive agents respectively enhances the ion / electron conductivity of the positive electrode side, thereby maximizing the charge transfer efficiency between the positive electrode active material and the outside world and fully releasing its capacity.
[0049] However, the solid electrolyte added to the positive electrode side is at risk of decomposition at high voltages (e.g., 3-5V) when in contact with the active material, and most traditional solid electrolytes have limited ion conductivity. When the solid electrolyte added is a sulfide, although it has relatively higher ionic conductivity, the risk of high-voltage decomposition is particularly significant due to the weak stability of sulfide. After high-pressure decomposition of the solid electrolyte, impurities with poor conductivity are produced, which reduces ionic conductivity, limits the improvement of the first-cycle coulombic efficiency, and reduces long-cycle performance. For high-gram capacity battery designs, the problem of electrolyte decomposition and damage is particularly severe because the proportion of electrolyte added is smaller, making it difficult to achieve stable long-term cycling.
[0050] In order to solve the above technical problems, the present application provides a positive electrode active material, which is formed by coating an ion-conducting layer containing a rare earth bromide solid electrolyte on at least a portion of the surface of a lithium transition metal oxide. While improving the ionic conductivity, it is also beneficial to improve the stability and high-voltage resistance, thereby improving the coulombic efficiency and cycle stability of the positive electrode active material and the all-solid-state battery using the positive electrode active material.
[0051] In a first aspect, the present application provides a positive electrode active material, comprising a lithium transition metal oxide and an ion-conducting layer coated on at least a portion of the surface of the lithium transition metal oxide, wherein the ion-conducting layer comprises a rare earth bromide solid electrolyte.
[0052] The positive electrode active material provided by the present application includes a lithium transition metal oxide and an ion-conducting layer, wherein the rare earth bromide solid electrolyte contained in the ion-conducting layer can not only improve the ionic conductivity of the lithium transition metal oxide, thereby improving its conductivity to active ions, thereby improving the coulombic efficiency of the positive electrode active material and the battery using the positive electrode active material. Moreover, since the rare earth bromide solid electrolyte has a relatively wider electrochemical window (wider than the sulfide solid electrolyte), it is more stable at high voltage, thereby effectively reducing the risk of high-voltage decomposition and improving the high-voltage resistance and cycle stability of the positive electrode active material and the battery using the positive electrode active material. Therefore, the positive electrode active material provided by the present application can take into account both ionic conductivity and high-voltage stability, which is conducive to achieving a simultaneous improvement in the coulombic efficiency and cycle stability of the battery.
[0053] It should be noted that the "active ions" mentioned in this application refer to ions that can be embedded and extracted back and forth between the positive and negative electrodes of the battery, such as lithium ions.
[0054] In some embodiments, the ion-conducting layer fully covers the lithium transition metal oxide.
[0055] The ion-conducting layer fully covers the lithium transition metal oxide, which is beneficial to further improve the high-voltage stability and cycle stability of the positive electrode active material and the positive electrode side, while widening the charge and discharge voltage range, thereby improving capacity performance.
[0056] In some embodiments, the rare earth bromide solid electrolyte satisfies the chemical formula Li 6-3x R x Br6, 0.5≤x≤1.5, R includes at least one of Sc, Y, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Optionally, 0.8≤x≤1.3.
[0057] For example, X-ray photoelectron spectroscopy (XPS) can be used to perform surface element analysis on the positive electrode active material of the present application, and the signal peaks corresponding to Li 1s, R 3d and Br 3d can be detected respectively, indicating the presence of rare earth bromide solid electrolyte in the ion-conducting layer, and the peak areas are S Li 、S R and S Br , use analytical software to convert the peak area into element concentration C Li 、C R and C Br , compared with C R and C Br , we can get the exact chemical formula of rare earth bromide solid electrolyte.
[0058] When the rare earth bromide solid electrolyte contained in the ion-conducting layer satisfies the above chemical formula, its ionic conductivity can reach the order of mS / cm, effectively improving the ion conduction efficiency of the ion-conducting layer and fully utilizing the capacity performance of the positive electrode active material. Furthermore, rare earth bromide solid electrolytes that meet the above chemical formula have a wider electrochemical window than sulfide solid electrolytes and are more stable on the positive electrode side, thereby effectively improving the coulombic efficiency and cycle stability of all-solid-state batteries.
[0059] In some embodiments, R includes at least one of Tb, Dy, Ho, Er, Tm, Yb, and Lu. Selecting these rare earth elements can further enhance the high-voltage resistance of the rare earth bromide solid electrolyte and the ion-conducting layer.
[0060] In some embodiments, the mass percentage of the rare earth bromide solid electrolyte in the positive electrode active material is 5% to 30%. For example, the mass percentage can be 5%, 7%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or any range thereof. Optionally, it can be 8% to 20%.
[0061] The mass proportion of rare earth bromide solid electrolyte in the positive electrode active material is within the above range, which can improve the ionic conductivity and high voltage stability while also enabling the positive electrode active material to have sufficiently high capacity performance.
[0062] For example, the mass proportion of the rare earth bromide solid electrolyte in the positive electrode active material can be tested by the following method: the positive electrode active material of the present application is digested with nitric acid, and the element ratios of Ni, Co, Mn, and R are measured by ICP-OES, so that the type of positive electrode active material and the ratio of Ni to R can be confirmed. The specific composition of the rare earth bromide solid electrolyte obtained by combining the above XPS results can be used to calculate the molar ratio of the positive electrode active material to the ion-conducting layer, and then the mass proportion of the rare earth bromide solid electrolyte in the positive electrode active material can be obtained.
[0063] In some embodiments, the molar amount of the lithium transition metal oxide is 5 to 80 times the molar amount of the bromide solid electrolyte, and can be 20 to 60 times.
[0064] In some embodiments, the thickness of the ion-conducting layer is 5 nm to 50 μm. For example, the thickness of the ion-conducting layer can be 5 nm, 7 nm, 10 nm, 15 nm, 20 nm, 50 nm, 100 nm, 500 nm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, or any range thereof. Optionally, the thickness can be 8 nm to 10 μm.
[0065] The thickness of the ion-conducting layer is within the above range, which is beneficial to further improve the structural stability and high-voltage resistance of the positive electrode active material, while maintaining its active ion conduction performance and capacity performance.
[0066] For example, the thickness of the ion-conducting layer can be tested by the following method: the positive electrode active material of the present application is uniformly dispersed in anhydrous ethanol, and after preparing a sample on a copper mesh, the thickness of the surface coating layer can be directly observed using a high-resolution transmission electron microscope (HRTEM), which is the thickness of the ion-conducting layer.
[0067] In some embodiments, the thicknesses of the ion-conducting layer corresponding to any two points on the outer surface of the ion-conducting layer are d1 and d2, respectively, and |d1-d2|≤20 nm.
[0068] The fact that |d1-d2| is within the above range indicates that the ion-conducting layer is more evenly distributed on the surface of the lithium transition metal oxide, that is, the ion-conducting layer more evenly coats the lithium transition metal oxide. This is beneficial to further enhance the high-voltage stability and cycle stability of the positive electrode active material and the positive electrode side, while broadening the charge and discharge voltage range, thereby improving capacity performance.
[0069] In some embodiments, the lithium transition metal oxide includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium cobalt oxide, lithium manganese oxide, and a lithium-rich manganese-based positive electrode material. Optionally, the lithium transition metal oxide is lithium nickel cobalt manganese oxide.
[0070] It should be noted that the mass percentage of lithium in the above-mentioned "lithium-rich manganese-based positive electrode material" is 8%~12%.
[0071] When lithium nickel cobalt manganese oxide is selected as the lithium transition metal oxide, by coating the surface of the lithium nickel cobalt manganese oxide with an ion-conducting layer containing a rare earth bromide solid electrolyte, the ionic conductivity and high-voltage stability of the positive electrode active material can be made relatively higher, thereby making the coulombic efficiency and cycle stability of the battery relatively better.
[0072] In some embodiments, the ionic conductivity of the lithium transition metal oxide is 10 -7 S / cm~10 -4 S / cm.
[0073] In some embodiments, the ionic conductivity of the positive electrode active material is 10 -6 S / cm~10 -3 S / cm.
[0074] The ionic conductivity of lithium transition metal oxides is 10 -7 S / cm~10 -4 S / cm, while the ionic conductivity of the positive electrode active material coated with the ion-conducting layer is 10 -6 S / cm~10 -3 S / cm, indicating that after being coated with the ion-conducting layer containing the rare earth bromide solid electrolyte, the ionic conductivity is effectively improved, which can effectively improve the coulombic efficiency.
[0075] In some embodiments, the volume average particle size of the positive electrode active material is 1 μm to 30 μm.
[0076] For example, the volume average particle size of the positive electrode active material can be conveniently measured with a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK, with reference to the particle size distribution laser diffraction method in GB / T 19077-2016.
[0077] Conventional coating methods for coating the surface of positive electrode active materials with solid electrolytes include dry coating, wet coating, electroplating, and vapor coating. However, these conventional coating methods often suffer from problems such as poor uniformity, large particle size, and high cost.
[0078] In order to overcome the above-mentioned defects of the current traditional coating method, in a second aspect, the present application provides a method for preparing a positive electrode active material, which can be used to prepare the positive electrode active material described in the first aspect of the present application, and specifically may include:
[0079] S1. Coating the rare earth bromide solid electrolyte on at least a portion of the surface of the lithium transition metal oxide to form the ion-conducting layer and prepare the positive electrode active material.
[0080] By coating at least part of the surface of a lithium transition metal oxide with a rare earth bromide solid electrolyte, not only can the ionic conductivity of the lithium transition metal oxide be improved, thereby enhancing its conductivity to active ions and, in turn, improving the coulombic efficiency of the positive electrode active material and the battery using the same, but also, because the rare earth bromide solid electrolyte has a relatively wider electrochemical window (wider than that of a sulfide solid electrolyte), it is more stable at high voltages, thereby effectively reducing the risk of high-voltage decomposition and improving the high-voltage resistance and cycling stability of the positive electrode active material and the battery using the same.
[0081] In some embodiments, coating the rare earth bromide solid electrolyte on at least a portion of the surface of the lithium transition metal oxide may include the following steps (see Figure 1 Schematic diagram of the preparation process shown):
[0082] S10, dissolving a rare earth compound and a lithium source in a hydrobromic acid solution to react to prepare a mixed solution containing a rare earth bromide and lithium bromide;
[0083] S20, adding ammonium bromide and lithium transition metal oxide to the mixed solution, drying, and pulverizing to prepare a mixture powder;
[0084] S30, performing vacuum heat treatment on the mixture powder to form a rare earth bromide solid electrolyte on at least a portion of the surface of the lithium transition metal oxide, and forming the ion-conducting layer covering at least a portion of the surface of the lithium transition metal oxide.
[0085] It should be noted that steps S10 to S30 described above are actually the preparation of the positive electrode active material through an ammonium-assisted synthesis method. It is understood that the "ammonium-assisted synthesis method" described in this application refers to the in-situ coating and preparation of the positive electrode active material using a lithium source and a rare earth compound as precursors, with the assistance of an ammonium salt.
[0086] The above-mentioned method provided in the present application utilizes an ammonium-assisted synthesis method to in situ prepare an ion-conducting layer on the surface of a lithium transition metal oxide and obtain a positive electrode active material, thereby achieving nanoscale coating of the ion-conducting layer, so that the prepared positive electrode active material has a smaller particle size and a higher uniformity; and the ammonium-assisted synthesis method has simple steps and low cost, which is conducive to large-scale preparation.
[0087] The ammonium-assisted synthesis method in the above-mentioned steps S10 to S30, by combining wet and dry coating processes, can achieve nano-synthesis of the ion-conducting layer and effectively improve the coating uniformity of the ion-conducting layer, while effectively improving the uniformity of the prepared positive electrode active material; and can achieve a uniformity and closer contact far exceeding the direct physical blending of lithium transition metal oxides and rare earth bromide solid electrolytes, which is beneficial to the improvement of the overall performance of the positive electrode active material.
[0088] In some embodiments, the mixture powder comprises the lithium transition metal oxide, ammonium bromide, lithium bromide, and rare earth bromide, and at least a portion of the surface of the lithium transition metal oxide is coated with the ammonium bromide, the lithium bromide, and the rare earth bromide.
[0089] In the wet coating step described in the above steps S10 and S20, a mixed solution containing rare earth bromide and lithium bromide is generated by reacting in a solution system, and the mixed solution is mixed with ammonium bromide and lithium transition metal oxide, dried and pulverized, so that the surface of the lithium transition metal oxide can be uniformly coated and the raw material of the ion-conducting layer can be formed, even if at least a portion of the surface of the lithium transition metal oxide is coated with the ammonium bromide, the lithium bromide and the rare earth bromide, and the particles of the raw material can be nanosized, thereby achieving a preliminary improvement in uniformity.
[0090] It is understood that the "pulverization" mentioned in this application refers to processing the dried bulk product to form a powder. Optionally, the processing of the dried bulk product includes grinding.
[0091] In some embodiments, the pH value of the hydrobromic acid solution in step S10 is 2-4.
[0092] By adjusting the pH value of the hydrobromic acid solution to 2-4, a suitable reaction environment can be provided for the reactions of the rare earth compound and the lithium source with hydrobromic acid. At the same time, the introduction of impurities into the final rare earth bromide solid electrolyte can be avoided, and the surface residual alkali of the lithium transition metal oxide can be effectively removed, thereby optimizing its performance.
[0093] In some embodiments, the rare earth compound includes a carbonate or oxide containing a rare earth element, for example, at least one of Sc2O3, Y2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, and Lu2O3, and Y2O3 may be selected.
[0094] In some embodiments, an excess amount of ammonium bromide is added in step S20, i.e., the molar ratio of ammonium bromide to the rare earth element in the rare earth compound is (3-8):1. For example, the molar ratio of the ammonium bromide to the rare earth element in the rare earth compound can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, or any range thereof, and can be (3-5):1.
[0095] It is understood that the mixed powder prepared in step S20 may still contain excess, unreacted rare earth compound. During the subsequent vacuum heat treatment in step S30, due to the strong oxygen affinity of rare earths, rare earth oxide impurities formed by the rare earth compound and oxygen are also produced alongside the final product. Subsequent high-temperature dehydration cannot completely desorb the oxygen and remove the rare earth oxide impurities, thereby affecting the ionic conductivity of the final product. However, due to the addition of excess ammonium bromide in step S20, i.e., the molar ratio of ammonium bromide to the rare earth element in the rare earth compound is controlled within the aforementioned range, the excess ammonium bromide decomposes at high temperatures to create an HBr gas atmosphere, which fully reacts with the rare earth oxide impurities produced with the final product, forming water vapor that is extracted by negative pressure. This achieves complete desorption of oxygen and complete removal of the rare earth oxide impurities, thereby reducing the impact of the rare earth oxide impurities on the ionic conductivity of the final product.
[0096] See also Figure 1 Schematic diagram of the preparation process. Since the excess ammonium bromide will re-condense in the ammonium recovery container after the reaction, it can be reused after simple purification processes such as filtration and evaporation. In addition, the temperature of the vacuum heat treatment does not exceed 500°C, which can achieve green synthesis of positive electrode active materials and achieve advantages such as high atomic utilization, low energy consumption and low cost.
[0097] In some embodiments, the lithium source includes, but is not limited to, lithium carbonate and lithium hydroxide.
[0098] In some embodiments, the lithium transition metal oxide includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium cobalt oxide, lithium manganese oxide, and a lithium-rich manganese-based positive electrode material. Optionally, the lithium transition metal oxide is lithium nickel cobalt manganese oxide.
[0099] The lithium transition metal oxide selected above can remain stable in the acidic environment of step S10 and at 500° C., so it can participate in the synthesis process of the rare earth bromide solid electrolyte without structural damage, which is beneficial to maintaining its electrochemical performance.
[0100] In step S30, the coating of the lithium transition metal oxide is carried out simultaneously with the synthesis of the rare earth bromide solid electrolyte, thereby achieving in-situ coating; and by extending the vacuum heat treatment time and increasing the temperature, a full reaction can be achieved. Among them, in-situ coating can achieve uniform coating at the nanoscale. Compared with ex-situ coating, if the bromide solid electrolyte is first synthesized using an ammonium-assisted synthesis method and then coated on the surface of the transition metal oxide by dry coating, it will make it difficult to achieve uniform coating at the nanoscale, and the process flow is relatively cumbersome.
[0101] In some embodiments, the temperature of the vacuum heat treatment is below 500°C, and can be optionally 430°C to 480°C.
[0102] In some embodiments, the vacuum heat treatment time is 2 hours to 6 hours, and can be optionally 3 hours to 4 hours.
[0103] By controlling the temperature of vacuum heat treatment below 500°C, it is beneficial to in situ generate rare earth bromide solid electrolyte on the surface of lithium transition metal oxide, thereby forming an ion-conducting layer; and utilizing the thermal disturbance generated at this temperature and the flow of ammonium bromide / hydrogen bromide vapor to promote further improvement of the uniformity of the ion-conducting layer, as well as further improvement of the uniformity of the prepared positive electrode active material.
[0104] Thus, the entire ammonium-assisted vacuum synthesis process utilizes the solution system in the preceding steps (i.e., steps S10-S20) to achieve initial uniformity improvement and nano-size particle size for the ion-conducting layer raw material. Furthermore, in the subsequent step (i.e., step S30), active thermal agitation and the flow of ammonium bromide / hydrogen bromide vapor further enhance uniformity and nano-size the ion-conducting layer. This results in a cathode active material with superior electrochemical performance.
[0105] This method can produce a nanoscale coating (i.e., an ion-conducting layer), resulting in a larger specific surface area. This facilitates charge transfer between the coated positive electrode active material and the outside world, enhancing its kinetic activity. Furthermore, the mechanical properties of the prepared positive electrode active material are superior to those of large-scale coated particles, which helps to extend its cycle life. Ultimately, the positive electrode active material prepared by this method can exhibit superior electrochemical performance in all-solid-state batteries, effectively improving the Coulombic first efficiency and cycle stability of all-solid-state batteries.
[0106] In a third aspect, the present application provides a composite positive electrode material, comprising the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect of the present application, and a first solid electrolyte.
[0107] In some embodiments, the first solid electrolyte includes an oxide-type solid electrolyte, a sulfide-type solid electrolyte, a halide-type solid electrolyte, and a polymer-type solid electrolyte, and may be a sulfide-type solid electrolyte.
[0108] In some embodiments, the sulfide-based solid electrolyte includes at least one of a binary compound such as Li2S-GeS2, Li2S-P2S5, or Li2S-SiS2, and a ternary compound such as Li2S-MeS2-P2S5 (Me = Si, Ge, Sn, Al, etc.), for example, Li6PS5Cl.
[0109] In some embodiments, in the composite positive electrode material, the mass ratio of the positive electrode active material to the first solid electrolyte is 70:(25-30).
[0110] In addition, the all-solid-state lithium secondary battery and the electric device of the present application will be described below with appropriate reference to the drawings.
[0111] Typically, an all-solid-state lithium secondary battery consists of a positive electrode, a negative electrode, and a solid electrolyte membrane. During the battery's charge and discharge processes, active ions are embedded and released back and forth between the positive and negative electrodes. The solid electrolyte membrane, located between the positive and negative electrodes, conducts ions and prevents short circuits between the positive and negative electrodes.
[0112] Positive electrode
[0113] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, the positive electrode active material layer includes the positive electrode active material of the first aspect of the present application, the positive electrode active material prepared by the method of the second aspect of the present application, and one of the composite positive electrode materials of the third aspect of the present application; the composite positive electrode material of the third aspect of the present application can be selected.
[0114] As a non-limiting example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.
[0115] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0116] In some embodiments, the positive electrode active material layer may optionally include a battery positive electrode active material known in the art. As non-limiting examples, the positive electrode active material may include one or more of the following materials: olivine-structured lithium-containing phosphates, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials; other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used singly or in combination. Examples of lithium transition metal oxides include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Non-limiting examples of olivine-structured lithium-containing phosphates include, but are not limited to, one or more of the following: lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.85 Co 0.15 Al 0.05 O2.
[0117] Given that the Li content in the cathode material changes, how should the subscript of Li be defined in the general formula?
[0118] For ternary materials:
[0119] Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , x is 0.2-1.2;
[0120] Li x A a (Ni a Co b Mn c ) 1-d M d O 2-y A y , x+a is 0.2-1.2.
[0121] For lithium manganese iron phosphate materials:
[0122] Li a Mn 1-y B y P 1-z C z O 4-n D n , a is 0-1.1;
[0123] Li a A x Mn 1-y B y P 1-z C z O 4-n D n , a+x is 0-1.1.
[0124] The above limitation on x includes the molar content of Li in different charge and discharge states of the battery (usually the battery voltage is between 2-5V).
[0125] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charge and discharge process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the list of positive electrode materials in this application, unless otherwise specified, the Li content is the initial state of the material. The positive electrode material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the Li content in the positive electrode material contained in the plate will usually change. Among them, the Li content can be measured by molar content, but is not limited to this. Regarding "the Li content is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that new materials obtained by appropriate modification on the basis of the listed positive electrode materials are also within the scope of positive electrode materials. The aforementioned appropriate modification refers to acceptable modification methods for positive electrode materials, and non-limiting examples include coating modification.
[0126] In the examples of positive electrode materials in this application, the oxygen (O) content is only a theoretical value. Lattice oxygen release will cause the molar content of oxygen to change, and the actual O content will fluctuate. The O content can be measured by molar content, but is not limited to this.
[0127] In some embodiments, the positive electrode active material layer may further optionally include a binder. As non-limiting examples, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0128] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0129] In some embodiments, the positive electrode sheet can be prepared by dispersing the components for preparing the positive electrode sheet, such as the positive electrode active material, conductive agent, binder, and any other components, in a solvent to form a positive electrode slurry; coating the positive electrode slurry on at least one side of the positive electrode current collector, and performing drying, cold pressing, and other processes to obtain the positive electrode sheet. The type of solvent can be selected from, but not limited to, any of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode current collector coated with the positive electrode slurry can be a single surface of the positive electrode current collector or both surfaces of the positive electrode current collector. The solid content of the positive electrode slurry can be 40 wt% to 80 wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000-25000 mPa·s. When applying the positive electrode slurry, the coating unit area density based on dry weight (excluding solvent) can be 15-35 mg / cm2 The compaction density of the positive electrode can be 3.0~3.6 g / cm 3 , optional range is 3.3~3.5 g / cm 3 .
[0130] Negative electrode
[0131] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0132] As a non-limiting example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.
[0133] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be obtained by forming a metal material on a polymer substrate. Non-limiting examples of the metal material in the negative electrode current collector may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Non-limiting examples of the polymer substrate in the negative electrode current collector may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0134] In some of these embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0135] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0136] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0137] In some embodiments, the negative electrode active material layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0138] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode current collector coated with the negative electrode slurry can be a single surface of the negative electrode current collector or two surfaces of the negative electrode current collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000-10000mPa·s. When coating the negative electrode slurry, the coating unit surface density based on dry weight (excluding solvent) can be 75-220 g / m 2 The compaction density of the negative electrode sheet can be 1.0 g / cm 3 ~ 1.8 g / cm 3 .
[0139] solid electrolyte membrane
[0140] The solid electrolyte membrane has the function of conducting ions between the positive electrode plate and the negative electrode plate. The solid electrolyte membrane of the present application is in a gel state or a fully solid state.
[0141] In some embodiments, the solid electrolyte membrane contains a second solid electrolyte, which includes at least one of an oxide-type solid electrolyte, a sulfide-type solid electrolyte, a halide-type solid electrolyte and a polymer-type solid electrolyte, and can be a sulfide-type solid electrolyte.
[0142] In some embodiments, the sulfide-based solid electrolyte includes at least one of a binary compound such as Li2S-GeS2, Li2S-P2S5, or Li2S-SiS2, and a ternary compound such as Li2S-MeS2-P2S5 (Me = Si, Ge, Sn, Al, etc.), for example, Li6PS5Cl.
[0143] In some embodiments, the solid electrolyte membrane may further include a lithium salt. The lithium salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0144] In addition, the present application also provides an electrical device, which includes the all-solid-state lithium secondary battery provided by the present application. The all-solid-state lithium secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.
[0145] As an electrical device, an all-solid-state lithium secondary battery can be selected according to its usage requirements.
[0146] Figure 2 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.
[0147] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0148] Example
[0149] Below, the embodiment of the present application is described. The embodiment described below is exemplary, is only used to explain the present application, and is not to be construed as limiting the present application. Where the technology or conditions are not specified in the embodiment, the technology or conditions described in the literature in this area or the product instructions are used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0150] Example 1
[0151] (1) Preparation of positive electrode active materials
[0152] When Ho2O3 and Li2CO3 with a molar ratio of 1:3 are dissolved in an excess of dilute hydrobromic acid solution (10wt%, pH=1~2), the Ho2O3 and Li2CO3 can be completely dissolved into Ho 3+ He Li +Regarding the amount of HBr, the amount of HBr in the dilute hydrobromic acid solution is approximately 10 at% excess. After the solution becomes clear, add NH₄Br in a molar amount equivalent to 3 times the molar amount of the Ho element. Once dissolved, add commercial NCM811 powder (Rongbai Technology, S800) in a molar amount equivalent to 50 times the molar amount of the Ho element. Thoroughly stir magnetically to form a suspension, then heat at 130°C to evaporate the solvent (H₂O) to obtain a solid precursor mixture.
[0153] The precursor mixture was ground into powder and transferred into a round bottom flask and Figure 1 The corresponding device was constructed as shown. After creating a vacuum environment using an oil pump and double-row pipes, a water pump was used to maintain the vacuum environment (approximately -0.1 MPa). Heat treatment was performed under vacuum and heating conditions at 450°C for 3 hours to produce a Li3HoBr6-coated NCM811 positive electrode active material.
[0154] (2) Preparation of all-solid-state lithium secondary batteries
[0155] The positive electrode active material prepared in (1) was mixed evenly with the first solid electrolyte Li6PS5Cl and the conductive agent VGCF (carbon fiber) in a mass ratio of 70:25:5 and then pressed into a layer to obtain a positive electrode active material layer.
[0156] A lithium-indium alloy sheet is used as the negative electrode.
[0157] Li6PS5Cl was used as the second solid electrolyte.
[0158] The positive electrode current collector (aluminum foil), the positive electrode active material layer, the second solid electrolyte and the negative electrode plate are assembled into an all-solid-state lithium secondary battery by pressure forming; the solid electrolyte membrane formed after pressing is 100 mg.
[0159] Example 2
[0160] The preparation of the positive electrode active material and the all-solid-state lithium secondary battery is similar to that in Example 1, with the main difference being that Ho2O3 is replaced by an equal mass of Tb2O3 to obtain a positive electrode active material of Li3TbBr6 coated NCM811.
[0161] Example 3
[0162] The preparation of the positive electrode active material and the all-solid-state lithium secondary battery is similar to that in Example 1, with the main difference being that the commercial NCM811 powder is replaced with an equimolar amount of lithium iron phosphate (LFP, LiFePO4) to prepare a Li3HoBr6-coated LFP positive electrode active material.
[0163] Examples 4-6
[0164] The preparation of the positive electrode active material and the all-solid-state lithium secondary battery is similar to that of Example 1, with the main difference being that the amount of NH4Br used is adjusted so that the molar ratios of NH4Br to Ho element are 1:1, 5:1, and 8:1, respectively.
[0165] Example 7
[0166] The preparation of the positive electrode active material and the all-solid-state lithium secondary battery is similar to that in Example 1, with the main difference being that the heat treatment temperature is 550°C.
[0167] Examples 8 to 13
[0168] The preparation of the positive electrode active material and the all-solid-state lithium secondary battery is similar to that in Example 1, with the main difference being that the amount of commercial NCM811 powder added during the preparation of the positive electrode active material is adjusted so that the mass proportions of the rare earth bromide solid electrolyte in the positive electrode active material are 5%, 10%, 12%, 15%, 20%, and 30%, respectively, and correspondingly, the thicknesses of the Li3HoBr6 coating layers are 5 nm, 10 nm, 20 nm, 50 nm, 10 μm, and 50 μm, respectively.
[0169] Comparative Example 1
[0170] The preparation of the all-solid-state lithium secondary battery is similar to that of Example 1, with the main difference being that the positive electrode active material in Example 1 is replaced by an equal mass of NCM811.
[0171] Comparative Example 2
[0172] The preparation of the all-solid-state lithium secondary battery is similar to that of Example 1, with the main difference being that the positive electrode active material in Example 1 is replaced by a positive electrode active material prepared by a conventional dry method of equal mass.
[0173] That is, the positive electrode active material is a positive electrode active material prepared by a traditional dry method in which Li3HoBr6 is coated on the surface of NCM811; the specific preparation steps include: taking NCM811 powder of the same mass as that in Example 1, mixing it with Li3HoBr6 powder equivalent to 2% of the mass of NCM811 powder, and then ball milling, the ball milling speed is 500 rpm, and the ball milling time is 24 hours.
[0174] Comparative Example 3
[0175] The preparation of the positive electrode active material and the all-solid-state lithium secondary battery is similar to that in Example 1, with the main difference being that dilute hydrobromic acid is replaced by dilute hydrochloric acid of equal molar amount and equal concentration, and NH4Cl is replaced by NH4Br of equal molar amount to prepare the positive electrode active material of Li3HoCl6 coated NCM811.
[0176] The relevant parameters of the positive electrode active materials of Examples 1 to 13 and Comparative Examples 1 to 3 are shown in Table 1 below, where “~” means approximately equal to, for example, “~8 μm” means “approximately equal to 8 μm”.
[0177] Table 1
[0178]
[0179] In addition, the positive electrode active materials and all-solid-state lithium secondary batteries obtained in Examples 1 to 13 and Comparative Examples 1 to 3 were subjected to performance tests. The test results are shown in Table 2 below.
[0180] Test section
[0181] (1) Ionic conductivity test
[0182] The positive electrode active material was subjected to EIS testing using an autolab electrochemical workstation to obtain its ionic conductivity data. The test temperature was 25°C and the frequency test range was 0.01~1MHz.
[0183] (2) 3C discharge specific capacity test
[0184] The full battery was tested on a blue power test platform at a temperature of 25°C and a voltage test range of 2.6~4.3V vs. Li + / Li, with a positive electrode areal capacity of 3 mAh / g. The full battery was cycled three times at a 0.1C charge rate and three times at different discharge rates, with a discharge rate range of 0.1C, 0.33C, 0.5C, 1C, 2C, and 3C, to obtain a 3C discharge specific capacity.
[0185] (3) Coulomb first effect and cycle capacity retention test
[0186] The full battery was tested on a blue power test platform at a temperature of 25°C and a voltage test range of 2.6~4.3V vs. Li + / Li, with a positive electrode surface capacity of 3 mAh / g. The full battery was cycled three times at 0.1C to 0.1C, followed by a long-term cycle test at 0.33C to 0.33C. The coulombic first efficiency at 0.1C and the cycle capacity retention at 0.33C were obtained, reflecting high-voltage stability.
[0187] Table 2
[0188]
[0189] In Table 2 above, it can be seen that the coulombic first effect and 200-cycle capacity retention rate of the embodiment are higher than those of comparative examples 1 and 2 by comparing the embodiment with comparative examples 1 and 2, indicating that compared with the traditional positive electrode active material and the positive electrode active material coated with rare earth bromide solid electrolyte prepared by the traditional dry method, the embodiment has a higher coulombic first effect and 200-cycle capacity retention rate, indicating that the positive electrode active material prepared by the method of the present application can effectively improve the coulombic efficiency and cycle stability of the battery. Comparing the embodiment with comparative example 3, it can be seen that the 200-cycle capacity retention rate of the embodiment battery is higher, indicating that compared with the positive electrode active material coated with rare earth chloride solid electrolyte, the positive electrode active material coated with rare earth bromide solid electrolyte of the present application has a higher ionic conductivity, thereby effectively reducing polarization and improving the cycle stability of the battery.
[0190] The above description of the various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced with each other and will not be repeated herein for the sake of brevity.
[0191] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that include: lithium transition metal oxides; and An ion-conducting layer is coated on at least a portion of the surface of the lithium transition metal oxide, and the ion-conducting layer comprises a rare earth bromide solid electrolyte.
2. The positive electrode active material according to claim 1, characterized in that The rare earth bromide solid electrolyte satisfies the chemical formula Li 6-3x R x Br6, 0.5≤x≤1.5, R includes at least one of Sc, Y, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu.
3. The positive electrode active material according to claim 1 or 2, characterized in that The mass proportion of the rare earth bromide solid electrolyte in the positive electrode active material is 5% to 30%, and can be optionally 8% to 20%.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The thickness of the ion-conducting layer is 5 nm to 50 μm, and can be optionally 8 nm to 10 μm.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that The lithium transition metal oxide comprises at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium cobalt oxide, lithium manganese oxide and lithium-rich manganese-based positive electrode materials; Optionally, the lithium transition metal oxide is lithium nickel cobalt manganese oxide.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that The ionic conductivity of the lithium transition metal oxide is 10 -7 S / cm~10 -4 S / cm.
7. The positive electrode active material according to claim 6, characterized in that The ionic conductivity of the positive electrode active material is 10 -6 S / cm~10 -3 S / cm.
8. The positive electrode active material according to any one of claims 1 to 7, characterized in that The volume average particle size of the positive electrode active material is 1 μm to 30 μm.
9. A method for preparing the positive electrode active material according to any one of claims 1 to 8, characterized in that: include: The rare earth bromide solid electrolyte is coated on at least a portion of the surface of the lithium transition metal oxide to form the ion-conducting layer to prepare the positive electrode active material.
10. The method according to claim 9, characterized in that Coating the rare earth bromide solid electrolyte on at least a portion of the surface of the lithium transition metal oxide comprises: performing vacuum heat treatment on a mixture powder comprising the lithium transition metal oxide, ammonium bromide, lithium bromide, and rare earth bromide to form the rare earth bromide solid electrolyte on at least a portion of the surface of the lithium transition metal oxide, and to form the ion-conducting layer covering at least a portion of the surface of the lithium transition metal oxide; Wherein, in the mixed powder, at least a portion of the surface of the lithium transition metal oxide is coated with the ammonium bromide, the lithium bromide and the rare earth bromide.
11. The method according to claim 10, characterized in that The preparation method of the mixture powder comprises: Dissolving a rare earth compound and a lithium source in a hydrobromic acid solution to react and prepare a mixed solution containing the rare earth bromide and the lithium bromide; The ammonium bromide and the lithium transition metal oxide are added to the mixed solution, followed by drying and pulverization to prepare the mixed powder.
12. The method according to claim 11, characterized in that The molar ratio of the ammonium bromide to the rare earth element in the rare earth compound is (3-8):
1.
13. The method according to claim 11 or 12, characterized in that The method satisfies at least one of the following conditions: (1) The pH value of the hydrobromic acid solution is 2-4; (2) The molar ratio of the ammonium bromide to the rare earth element in the rare earth compound is (3-5):1; (3) The temperature of the vacuum heat treatment is below 500°C, and can be selected from 430°C to 480°C.
14. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 8 or the positive electrode active material prepared by the method according to any one of claims 9 to 13.
15. An all-solid-state lithium secondary battery, characterized in that: Including the positive electrode sheet according to claim 14.
16. An electrical device, characterized in that: Including the all-solid-state lithium secondary battery according to claim 15.